Economics of Wildlife Tourism and Its Challenges: A Case Study of Nimule National Park, South Sudan - Mayele, Joseph Mayindo; Takeshi, Sakurai; Saburi, Emmanuel Joel (American Journal of Management, 2023)
Wildlife tourism plays an important role in the generation of foreign revenues in many developing countries, although its role is becoming increasingly less feasible. This study sought to determine the economics of wildlife tourism between 2009-2014 and the communities’ perception of Nimule National Park (NNP). A randomly collected cross-sectional survey data of 300 participants were used and the descriptive and inferential analyses were done using PAST statistical software program. The results showed total income generated between 2009 and 2014 was 21,548.15 USD, with 2012 earning the largest share (10,319 USD). 92% of tourists who visited NNP were foreigners, majorly for wildlife watching (48%) and photographing. Local communities’ benefits were wild fruits and fuelwood collection. About 60% of respondents opposed park entry charges, although most were subjective. Human-wildlife conflicts (73.8%) and poor infrastructure (66.4%) were the communities’ and park’s challenges. Notwithstanding the unexpected conflict in 2013, the tourism sector can still be promising with genuine peace or security in the country.